Cronodent I, 3D interactive manual for self-learning of the dental chronology of equines - Rodero, Evangelina; González-Martínez, Ana; Diz, Andres; Rodero, Jesus (Frontiers in Veterinary Science, 2025)
One of a veterinarian’s routine tasks is animal identification, with age being a crucial factor in the identification and evaluation of individuals. Knowledge of the morphological changes in animal dentition used to determine their age is essential in veterinary education. Today’s students increasingly prefer innovative learning tools that incorporate 3D anatomical models over traditional 2D resources. As part of a teaching innovation project at the University of Córdoba, Spain, new educational materials were developed to aid students in identifying the age of animals using 3D images of equine incisor teeth. The main objectives of this initiative were to develop an app, Cronodent I, to support learning of equine dental chronology through 3D-scanned images of horses’ dental arches. A second objective was to evaluate students’ perception and acceptance of these new teaching materials, as well as their impact on academic performance. For this purpose, 17 equine dental arches were 3D scanned and incorporated into the Cronodent I app. The app’s usefulness was evaluated through a student satisfaction survey (N = 97) and, success rate and performance scores (N = 453). The app was easily accessible and received positive ratings for functionality and usability. The scores improved significatively (p < 0.05) from 4.37 to 4.86, following the success rate a similar trend: it increased more after the Cronodent I app became available to students on the Moodle platform (50.35% vs. 57.51%), but dropped to 48.76% when the app was accessible only on Android mobile devices. Cronodent I proved to be an effective educational tool for developing students’ skills in determining horse age based on dentition type and tooth wear stages. Cronodent I supports self-directed learning and offers mobile access to anatomical materials and resources, with accessibility emerging as a key factor in its overall success. Further research is needed to assess the long-term impact of Cronodent I on the learning outcomes of veterinary students to determine its effectiveness.